“Passorong Tedong” As A Requirement For The Validity Of Marriage According To The Tuho Law In Ulumanda District Majene Regency - Ika Novitasari (Kirana Publisher (KNPub), 2022)
Marriage is defined as a very strong contract or miistaaqan gholiidhan to obey God's commands and its implementation is a form of worship. In Islamic law, marriage is considered valid if the pillars and conditions of a valid marriage are met. These two elements are very basic and cannot be abandoned. However, in the Ulumanda District, the community imposes conditions other than those specified by the Shari'a and the Islamic Law Compilation. The condition is